PENAFSIRAN HERMENEUTIKA KH. MUSTAIN SYAFI’I DALAM TAFSIR AL-QUR’AN AKTUAL DI WEBSITE WWW.BANGSAONLINE.COM PADA QS. THAHA: 63-64 (Studi Analisis Hermeneutika Obyektif Emilio Betti): Studi Analisis Hermeneutika Obyektif Emilio Betti - Aminatul Khusnah; Salamah Noorhidayati (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
Along with the current development of the flow of information and mass media and communication that is so fast and sometimes the information that comes in is very fast and allows for confusion of facts which results in distortion of facts. With the development of communication and information media, it will certainly be closely related to the increasingly effective and dynamic process of scientific transformation. The interpretation tradition has also experienced developments in various fields, one of which is in the field of methodology, which uses the hermeneutic method. The meaning interpretation theory approach comes from Emilio Betti's hermeneutic theory, namely meaning interpretation initiated by Emilio Betti which emphasizes more on the reconstruction of meaning armed with the intellectual horizon of the interpreter (subject) Emilio Betti's hermeneutic theory as a means of interpreting Al-Qur'anic verses. One of them is the Actual Tafsir which is one of the works of Indonesian scholars, namely KH. Mustain Syafi'i, in the writing process, uses online newspapers on an online website (www.bangsaonline.com). So this paper presents how hermeneutical reasoning is conveyed by KH. Mustain Syafi'i in the interpretation of the QS Thaha verses 63-64 which he did on the online website. This research uses literature studies and literature reviews using journals, books, and others according to the research theme as the main data in this research.